Experimental device-independent efficient certification of unsharp measurements - Wei Zhou; Xinhui Li; Ran Yang; Linrunde Tao; Yi-Chen Liu; Zhenda Xie; Yan-Xiao Gong; Shi-Ning Zhu (Physical Review Research)
Unsharp measurement is a unique type of measurement which provides a tradeoff between information gain and state disturbance. Such measurement is a crucial method in quantum theory and shows potential in various applications. We propose a device-independent scheme for certifying unsharp measurements with binary outcome in an efficient manner. Our scheme has low consumption of measurement resources and is robust against noise. In experiment, we demonstrate the certification of a typical kind of unsharp measurements. We achieve high fidelities above 0.9 when the strength of the unsharp measurement is less than 0.6 and get near unity fidelities in the low measurement strength range. Our scheme can be applied to enhance the feasibility and practicability of device-independent quantum information processing tasks.